Antidepressants, Depression, and Venous Thromboembolism Risk: Large Prospective Study of UK Women. Issue 5 (May 2017) - Parkin, Lianne; Balkwill, Angela; Sweetland, Siân; Reeves, Gillian K.; Green, Jane; Beral, Valerie; ,
Abstract : Background: Some investigators have reported an excess risk of venous thromboembolism (VTE) associated with depression and with use of antidepressant drugs. We explored these associations in a large prospective study of UK women. Methods and Results: The Million Women Study recruited 1.3 million women through the National Health Service Breast Screening Programme in England and Scotland. Three years after recruitment, women were sent a second questionnaire that enquired about depression and regular use of medications in the previous 4 weeks. The present analysis included those who responded and did not have prior VTE, cancer, or recent surgery. Follow‐up for VTE was through linkage to routinely collected National Health Service statistics. Cox regression analyses yielded adjusted hazard ratios and 95% CIs. A total of 734 092 women (mean age 59.9 years) were included in the analysis; 6.9% reported use of antidepressants, 2.7% reported use of other psychotropic drugs, and 1.8% reported being treated for depression or anxiety but not use of psychotropic drugs. During follow‐up for an average of 7.3 years, 3922 women were hospitalized for and/or died from VTE. Women who reported antidepressant use had a significantly higher risk of VTE than women who reported neither depression nor use of psychotropic drugs (hazard ratio, 1.39; 95% CI, 1.23–1.56). VTE risk was not significantly increased in women who reported being treated for depression or anxiety but no use of antidepressants or other psychotropic drugs (hazard ratio, 1.19; 95% CI, 0.95–1.49). Conclusions: Use of antidepressants is common in UK women and is associated with an increased risk of VTE.